Measurements of entrance-surface vs. conventional single-ended readout of a monolithic scintillator - Hunter, William C. J. (2011)
Availability of compact high-gain, low-noise Silicon Photomultipliers (SiPM) prompts us to examine readout sensors on the entrance surface (SES) as compared to the conventional single-ended readout with sensors on the opposing surface. We measured detector response statistics versus 3D position for these configurations using an 8×8 SiPM array on a 15-mm-thick by 32-mm-wide LYSO block. We calibrate an independently distributed multivariate-normal likelihood model and use it to generate maximum-likelihood estimates of 3D interaction position. Spatial resolution improved 14% and timing resolution improved 10% for the SES device. Bias was unaffected. Photodetection efficiency of our prototype SiPM may have limited further improvement in positioning and timing performance. In future work, we will look to utilize SiPM arrays with enhanced photodetection efficiency.